2016
DOI: 10.1055/s-0036-1584575
|View full text |Cite
|
Sign up to set email alerts
|

Low Albumin Is a Risk Factor for Complications after Revision Total Knee Arthroplasty

Abstract: Low serum albumin has been shown in the primary joint arthroplasty setting to increase the rate of perioperative complications. Our present work examined a large national inpatient administrative dataset to study the relationship between serum albumin level and key outcome measures after revision total knee arthroplasty (RTKA). Our hypothesis was that lower serum albumin would be an independent risk factor for poor outcomes after RTKA. We analyzed the American College of Surgeons National Surgical Quality Impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…In this cohort, hypoalbuminaemia was present in 17.36% of patients with femoral neck fracture on admission to the hospital. The incidence of hypoalbuminaemia observed in our cohort of patients is similar to what Kamath A, et al 20 reported in their study. They examined 4551 consecutive patients admitted for revision total knee arthroplasty and found hypoalbuminaemia in 16.1% of patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this cohort, hypoalbuminaemia was present in 17.36% of patients with femoral neck fracture on admission to the hospital. The incidence of hypoalbuminaemia observed in our cohort of patients is similar to what Kamath A, et al 20 reported in their study. They examined 4551 consecutive patients admitted for revision total knee arthroplasty and found hypoalbuminaemia in 16.1% of patients.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have indicated that preoperative hypoalbuminaemia is a well-documented risk factor for postoperative complications in various types of surgery. 17,25 Kamath A et al 20 reported that hypoalbuminaemia was independently associated with an increased risk of developing deep organ surgical-site infections, surgical-site infections, urinary traction infections, pneumonia and sepsis after revision total knee arthroplasty. Rungsakulkij N et al 15 reported that perioperative albumin was an important factor associated with serious complications following pancreaticoduodenectomy, include POP.…”
Section: Discussionmentioning
confidence: 99%
“…The current study con rmed that perioperative hypoalbunemia was an important risk factors for wound complications following single-segment PLIF surgery [22][23][24][25][26][27]. Our study further con rmed that perioperative hypoalbuminemia are important risk factors for SWD and SSI.…”
Section: Discussionsupporting
confidence: 76%
“…The authors drew encouragement from these findings since hypoalbuminemia may be more easily modifiable than other risk factors ( e.g ., morbid obesity). Results from two subsequent studies also involving thousands of patients undergoing TKA (primary[61] or revision[62]) were consistent with these findings.…”
Section: Other Indicationsmentioning
confidence: 53%